2019
DOI: 10.1111/jace.16635
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and microstructure development of Yb:YAG transparent ceramics from co‐precipitated powders without additives

Abstract: Sintering additives are generally considered to be important for improving densification in fabrication of transparent ceramics. However, the sintering aids as impurities doped in the laser materials would decrease the laser output power and produce additional heat during laser operation. In this work, Yb:YAG ceramics were vacuum‐sintered without additives at different temperatures for various soaking time through using ball‐milled powders synthesized by co‐precipitation route. The densification behavior and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…[7][8][9] For the laser ceramic hosts, the most widely studied garnet is the yttrium aluminum garnet Y 3 Al 5 O 12 (YAG). 10,11 The first significant breakthrough in the transparent ceramic is the Nd:YAG ceramics, which was first successfully fabricated by the solid-state reactive method by Ikesue et al in 1995. 12,13 In order to increase the bandwidth of the absorption and emission peaks of the Yb:YAG ceramics for the ultra-faster and broader tunable laser generation, the mixed garnets media were proposed and prepared.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] For the laser ceramic hosts, the most widely studied garnet is the yttrium aluminum garnet Y 3 Al 5 O 12 (YAG). 10,11 The first significant breakthrough in the transparent ceramic is the Nd:YAG ceramics, which was first successfully fabricated by the solid-state reactive method by Ikesue et al in 1995. 12,13 In order to increase the bandwidth of the absorption and emission peaks of the Yb:YAG ceramics for the ultra-faster and broader tunable laser generation, the mixed garnets media were proposed and prepared.…”
Section: Introductionmentioning
confidence: 99%
“…For the laser ceramic hosts, the most widely studied garnet is the yttrium aluminum garnet Y 3 Al 5 O 12 (YAG) 10,11 . The first significant breakthrough in the transparent ceramic is the Nd:YAG ceramics, which was first successfully fabricated by the solid‐state reactive method by Ikesue et al.…”
Section: Introductionmentioning
confidence: 99%
“…Tetraethyl orthosilicate (TEOS) is a commonly used sintering additive to promote the densification of YAG ceramics. [19][20][21][22][23] Boulesteix et al 24 reported that the densification rate obtained by adding .3 wt.% SiO 2 was two orders of magnitude higher than pure YAG powder. A small amount of SiO 2 doping can significantly increase the densification rate of YAG ceramics, whereas SiO 2 doping exceeding a critical amount may result in the formation of a second phase abundant in Si, which is vulnerable to fluorine gas etching.…”
Section: Introductionmentioning
confidence: 99%
“…Tetraethyl orthosilicate (TEOS) is a commonly used sintering additive to promote the densification of YAG ceramics 19–23 . Boulesteix et al 24 .…”
Section: Introductionmentioning
confidence: 99%